AJARAN TRI N UNTUK MENGEMBANGKAN KREATIVITAS SISWA DALAM PEMBELAJARAN IPS - Ulviyani, Reni; Wachid, Al’amin; Karnila Widiastuti, Kiki; Maria Zulfiati, Heri (Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas PGRI Yogyakarta, 2023)
This study aims to increase students' creativity by applying Tri N teachings (niteni, niroake, nambahake) through social studies learning in elementary schools. The instruments used were observation sheets of the learning process and observation sheets or observation rubrics for the level of student creativity. While the interview technique is used to obtain data related to Tri N teachings to students. Students' creative attitudes were observed using the observation rubric. Tri N is one of the Tamansiswa teachings initiated by Ki Hajar Dewantara. The research method used is descriptive qualitative to describe Tri N learning in an effort to increase the creativity of class VI A students at SDN 2 Banjarpasar. While the data collection techniques used include observation, interviews, and the creative attitude observation rubric. The data analysis technique used refers to Milles and Huberman which includes the process of data reduction, presentation, and drawing conclusions. The results of the research that has been done show that the application of Tri N teachings makes students have high creativity so that they can produce innovative and creative works.